2019
DOI: 10.1097/bot.0000000000001514
|View full text |Cite
|
Sign up to set email alerts
|

Bifocal Compression–Distraction for Combined Bone and Soft-Tissue Defects in Post-traumatic Tibial Nonunion

Abstract: Objective: To compare 2 distraction osteogenesis techniques in post-traumatic tibial nonunion patients with composite bone and soft-tissue defects. Design: Nonrandomized prospective, case series, single-center study. Setting: Department of Orthopaedics and Traumatology, Limb Reconstruction Unit, El-Helal hospital, Cairo, Egypt. Participants: Fifty post-traumatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
0
23
0
1
Order By: Relevance
“…Previously, the Ilizarov external fixation technique was the most commonly used technique for large bone defects without soft tissue defects [8,22]. In recent years, an increasing number of studies have reported that bone transport with external fixation can be used to simultaneously treat massive bone and soft tissue defects [5,9,23,24]. The technique of bone transport combined with soft-tissue transport (open bone transport) was first proposed by Suger [25].…”
Section: Bone Transport Combined With Soft-tissue Transport (Open Bonmentioning
confidence: 99%
“…Previously, the Ilizarov external fixation technique was the most commonly used technique for large bone defects without soft tissue defects [8,22]. In recent years, an increasing number of studies have reported that bone transport with external fixation can be used to simultaneously treat massive bone and soft tissue defects [5,9,23,24]. The technique of bone transport combined with soft-tissue transport (open bone transport) was first proposed by Suger [25].…”
Section: Bone Transport Combined With Soft-tissue Transport (Open Bonmentioning
confidence: 99%
“…The autogenous bone grafting at the docking site was recommended to perform when the distraction stage finished [3,23,[25][26][27]. Wan et al [28] showed a series of 28 femoral bone defects treated by bone transport using a monolateral external fixator combined with bone grafting at the docking site, and obtained a good bone healing rate of 92.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the Ilizarov external xation technique was the most commonly used technique for large bone defects without soft tissue defects [8,20]. In recent years, an increasing number of studies have reported that bone transport with external xation can be used to simultaneously treat massive bone and soft tissue defects [5,9,21,22]. The technique of bone transport combined with soft-tissue transport (open bone transport) was rst proposed by Suger [23].…”
Section: Discussionmentioning
confidence: 99%